OPTIMIZATION DEFENSE INDUSTRY MASTER TO STRENGTHEN DEFENSEMARITIME IN THE ORDER TO REALIZE INDONESIA AS WORLD MARITIME AXIS - Suwandi Suwandi; Suryoko Suryoko; Rina Marlina (JOURNAL ASRO, 2021)
In designing the development of the national defense posture, developing doctrine, and developing defense strategies, both military and non-military, to support national defense, it is necessary to have a strong and reliable state defense system with a universal defense management system that involves all citizens, territories and national resources which is carried out sustainably in order to uphold state sovereignty, territorial integrity and national safety with efforts made between other :1) The Indonesian nation must realize and see itself as a nation whose identity, prosperity and future are largely determined by managing the oceans, 2) Commitment to maintain and manage national marine resources, 3) Build maritime infrastructure and connectivity, 4) Maritime diplomacy as the main pillar in free and active diplomacy and 5) Organizing national defense with maritime defense forces and Increasing the capacity of maritime human resources. Keywords: Mastery of the Defense Industry, Maritime Defense and Indonesia Maritime Axis.